Practical quality improvement changes for a low-resourced pediatric unit - Yager, Phoebe H.; Callans, Kevin Mary; Samost-Williams, Aubrey; Bonilla, Jose A.; Flores, Luis J. G.; Hasbun, Susana C. A.; Rodríguez, Angel E. A.; Cárdenas, Alejandra B. A.; Núñez, Alexia M. L.; Jayawardena, Asitha D. L.; Zablah, Evelyn J.; Hartnick, Christopher J. (Frontiers in Public Health, 2024)
This work utilizes a Driver Map and Impact Pathway model to demonstrate the various levers and process improvement measures that can be focused upon to reduce child mortality in a low and middle resourced countries .There is little empirical evidence regarding long-term effects from ongoing pediatric global health process improvement and QI programs.This study applies such drivers and Impact models to identify components for a QI intervention designed to reduce child mortality in low and middle resourced countries, which produced a persistent decrease in child mortality.